2007
DOI: 10.1038/sj.jid.5700820
|View full text |Cite
|
Sign up to set email alerts
|

HaCaT Keratinocytes Overexpressing the S100 Proteins S100A8 and S100A9 Show Increased NADPH Oxidase and NF-κB Activities

Abstract: The calcium- and arachidonic acid (AA)-binding proteins S100A8 and S100A9 are involved in nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation in phagocytes. They are specifically expressed in myeloid cells, and are also found in epithelial cells in various (patho)physiological conditions. We have investigated the consequences of S100A8/A9 overexpression in epithelial cell lines on reactive oxygen species (ROS) generation and downstream signaling. Epithelial carcinoma HeLa cells, which exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 82 publications
3
84
1
1
Order By: Relevance
“…20 In line with this observation, we found that S100A8 and S100A9 co-expression enhances ROS levels in HCC cells that were even more pronounced in TNF-␣-stimulated cells. Numerous studies demonstrate a causal link between ROS and molecular mechanisms of liver carcinogenesis and defined ROS as a common denominator of signaling pathways induced by different HCC-promoting agents.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…20 In line with this observation, we found that S100A8 and S100A9 co-expression enhances ROS levels in HCC cells that were even more pronounced in TNF-␣-stimulated cells. Numerous studies demonstrate a causal link between ROS and molecular mechanisms of liver carcinogenesis and defined ROS as a common denominator of signaling pathways induced by different HCC-promoting agents.…”
Section: Discussionsupporting
confidence: 85%
“…There is evidence that enhanced production of ROS is a common response to all described HCCinducing causes. Because S100A8 and S100A9 overexpression in HaCaT keratinocytes (immortalized human keratinocytes) increases nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity and enhances ROS levels, 20 we asked whether elevated S100A8 and S100A9 protein levels induce ROS production also in HCC cells. Hep3B cells were transfected with S100A8 and S100A9 expression plasmids, and ROS levels were measured by DCFDA fluorescence staining using flow cytometry analysis.…”
Section: S100a8 and S100a9 Expression In Hepatocellular Carcinoma Celmentioning
confidence: 99%
“…Low levels of ROS may induce the proliferation of different cell types specifically endothelial cells [39]. In HaCaT keratinocytes overexpression of S100A8 and S100A9 promoted NADPH oxidase activation followed by higher levels of ROS generation [40]. We hypothesized that psoriasin may induce low levels of ROS by a similar mechanism, leading to a further increase in ROS levels, VEGF expression and cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8 and S100A9 are predominately expressed in cells of the myeloid lineage. Beside their constitutive expression in myeloid cells, they are expressed in epithelial cells in response to stress [14,15]. Their expression is transiently induced in keratinocytes after epidermal injury [16,17], after UVB irradiation [18], and in response to proinflammatory cytokines such as TNFa and IL1b [14].…”
Section: Introductionmentioning
confidence: 99%
“…Beside their constitutive expression in myeloid cells, they are expressed in epithelial cells in response to stress [14,15]. Their expression is transiently induced in keratinocytes after epidermal injury [16,17], after UVB irradiation [18], and in response to proinflammatory cytokines such as TNFa and IL1b [14]. Data showing that the two S100 proteins are up regulated by the putative TLR ligand LPS are conflicting [19,20].…”
Section: Introductionmentioning
confidence: 99%